2022
DOI: 10.14814/phy2.15546
|View full text |Cite
|
Sign up to set email alerts
|

Reduced oxygen saturation entropy is associated with poor prognosis in critically ill patients with sepsis

Abstract: Recent studies have found that oxygen saturation (SpO 2 ) variability analysis has potential for noninvasive assessment of the functional connectivity of cardiorespiratory control systems during hypoxia. Patients with sepsis have suboptimal tissue oxygenation and impaired organ system connectivity. Our objective with this report was to highlight the potential use for SpO 2 variability analysis in predicting intensive care survival in patients with sepsis. MIMIC-III clinical data of 164 adults meeting Sepsis-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This is further supported by physiological network disconnections along pH-associated axes, which predict mortality independent of SOFA score and KCC. Indeed, the strength of network analysis is the ability to assess the interactions of multiple organ systems in critically ill patients where the risk of multiple organ failure is high and similar findings continue to show significant promise [80,81]. Future studies could benefit from using a multicentre, multinational cohort of ALF patients to validate the findings herein.…”
Section: Discussionmentioning
confidence: 80%
“…This is further supported by physiological network disconnections along pH-associated axes, which predict mortality independent of SOFA score and KCC. Indeed, the strength of network analysis is the ability to assess the interactions of multiple organ systems in critically ill patients where the risk of multiple organ failure is high and similar findings continue to show significant promise [80,81]. Future studies could benefit from using a multicentre, multinational cohort of ALF patients to validate the findings herein.…”
Section: Discussionmentioning
confidence: 80%
“…Further, variability (entropy) in oxygen saturation (SpO 2 ) was recently assessed by Gheorghita et al. ( 2022 ) in critically ill patients with sepsis showing that SpO 2 entropy can predict mortality independent of Age, SOFA score, and mean SpO 2 . This work corroborated a previous work by Bhogal and Mani ( 2017 ) which showed that variability in oxygen saturation carries information about organ systems uncoupling that possibly drives aging.…”
Section: Network Physiology In Other Diseasesmentioning
confidence: 99%
“…This failure to adapt or respond appropriately can be transient and mild, or it can be devastating, as with sepsis and multiple organ failure (Buchman, 2006 ; Ivanov, 2021 ). Reduced complexity in physiological variables such as cardiac rhythm (Satti et al., 2019 ), blood oxygen saturation (Al Rajeh et al., 2021 ; Gheorghita et al., 2022 ), and skin or core body temperature (Bottaro et al., 2020 ; Mowery et al., 2011 ) is associated with increased mortality. Further, reduced functional connectivity between organ systems significantly and independently predicts survival in cirrhosis (Oyelade et al., 2023 ; Zhang et al., 2022 ) or sepsis (Asada et al., 2016 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…entropy) describes the level of apparent disorder within a system. Low signal complexity predicts unfavorable outcome in a variety of diseases and is assumed to reflect increased rigidity of the cardio/cerebrovascular feedback/regulating system leading to (or reflecting) autoregulation failure [9][10][11][12] This, in turn, leaves the brain susceptible to secondary injury. Physiological systems are regulated by multiple, interacting, mechanisms leading to dynamically changing biosignals across different temporal scales.…”
Section: Introductionmentioning
confidence: 99%